Fatty acid and phenolic profiles of almond grown in Serbia. (1st November 2017) - Čolić, Slavica D.; Fotirić Akšić, Milica M.; Lazarević, Kristina B.; Zec, Gordan N.; Gašić, Uroš M.; Dabić Zagorac, Dragana Č.; Natić, Maja M.
Highlights: Fatty acid and phenolics of almonds grown in Serbia were reported for the first time. The most abundant fatty acids were oleic acid and linoleic acid. The predominant polyphenol was catechin, followed by chlorogenic acid and naringenin. Each of the 23 almond samples was characterized by a unique phenolic profile. Abstract: Almond production is not typical for Serbia however the existence of natural populations and unexpectedly suitable agro-climatic conditions initiated this kind of study. Total oil content and concentrations of the fatty acids, total phenolic content and radical-scavenging activity were determined in the kernel oil of 20 local almond selections originating from North Serbia and cultivars 'Marcona', 'Texas' and 'Troito'. Sixteen fatty acids were identified and quantified, with the most abundant being oleic acid and linoleic acid. Nine phenolic acids and nineteen flavonoids were quantified using UHPLC-DAD MS/MS. The predominant polyphenol was catechin, followed by chlorogenic acid and naringenin. Based on oleic acid/linoleic acid ratio, levels of unsaturated fatty acids and specific polyphenols, some selections were chosen for growing and could also be recommended for breeding programs. Our investigation demonstrated that this region could be a suitable for growing almonds with chemical compositions competitive with standard cultivars.